Influence of Ocean Acidification on the Organic Complexation of Iron and Copper in Northwest European Shelf Seas; a Combined Observational and Model Study - Avendaño, Lizeth; Gledhill, Martha; Achterberg, Eric P.; Rérolle, Victoire M. C.; Schlosser, Christian (Frontiers in Marine Science, 2016)
The pH of aqueous solutions is known to impact the chemical speciation of trace metals. In this study we conducted titrations of coastal seawaters with iron and copper at pH 7.91, 7.37 and 6.99 (expressed on the total pH scale). Changes in the concentration of iron and copper that complexed with the added ligands 1-nitroso-2-napthol and salicylaldoxime respectively were determined by adsorptive cathodic stripping voltammetry - competitive ligand equilibrium (AdCSV-CLE). Interpretation of the results, assuming complexation by a low concentration of discrete ligands, showed that conditional stability constants for iron complexes increased relative to inorganic iron complexation as pH decreased by approximately 1 log unit per pH unit, whilst those for copper did not change. No trend was observed for concentrations of iron and copper complexing ligands over the pH range examined. We also interpreted our titration data by describing chemical binding and polyelectrolytic effects using non-ideal competitive adsorption in Donnan-like gels (NICA-Donnan model) in a proof of concept study. The NICA-Donnan approach allows for the development of a set of model parameters that are independent of ionic strength and pH, and thus calculation of metal speciation can be undertaken at ambient sample pH or the pH of a future, more acidic ocean. There is currently a lack of basic NICA-Donnan parameters applicable to marine dissolved organic matter (DOM) so we assumed that the measured marine dissolved organic carbon could be characterized as terrestrial fulvic acids. Generic NICA-Donnan parameters were applied within the framework of the software program visual MINTEQ and the metal –added ligand concentrations [MeAL] calculated for the AdCSV-CLE conditions. For copper, calculated [MeAL] using the NICA-Donnan model for DOM were consistent with measured [MeAL], but for iron an inert fraction with kinetically inhibited dissolution was required in addition to the NICA-Donnan model in order to approximate the trends observed in measured [MeAL]. We calculated iron and copper speciation in Northwest European shelf water samples at ambient alkalinity and projected increased pCO2 concentrations as a demonstration of the potential of the approach.